Effect of The Use of Interactive Multimedia Learning Media on Student Learning Outcomes (Quasi-Experimental Study on Theme Subtema 2 of Grade IV Science Content in Lebakwangi Elementary School 2, Kuningan District) - Hermawati, Eli; Eliyanti, Marlina; Setiawan, Aris (International Conference on Elementary Education, 2020)
The background in this study is that there is a problem in student learning outcomes in the cognitive realm of science content caused by the use of learning media that are less varied. This study aims to determine (1) differences in learning outcomes between students who use interactive multimedia learning media in the experimental class with students who use powerpoint media after getting treatment in the control class, (2) the difference in gain of student learning outcomes using media interactive multimedia learning in the experimental class with students using powerpoint learning media in the control class. The type of research used in this study was quasi-experimental with nonequivalent control group design. The number of students in class 4A 24 students and 4B class 24 students. The data collection used in this study was a test instrument in the form of 20 multiple choice questions. The data analysis used is differential statistical analysis and inferential statistical analysis. The results showed (1) there were differences in student learning outcomes using interactive multimedia learning media with students using powerpoint learning media, (2) there were differences in improvement in student learning outcomes using interactive multimedia learning media with students using powerpoint learning media. The implication in this study is that interactive multimedia learning media are more effectively used in the subject of style influences. The researcher suggested that it would be better when the learning process was carried out as interesting as possible